The Cost-Effectiveness of Closed Incisional Negative Pressure Wound Therapy for Infection Prevention after Revision Total Knee Arthroplasty - Pagani, Nicholas R.; Moverman, Michael A.; Puzzitiello, Richard N.; Menendez, Mariano E.; Kavolus, Joseph J. (The Journal of Knee Surgery, 2021)
Recent investigations have shown that closed incisional negative pressure wound therapy (ciNPWT) decreases the rate of postoperative wound complications following revision total knee arthroplasty (TKA). In this study, we used a break-even analysis to determine whether ciNPWT is a cost-effective measure for reducing prosthetic joint infection (PJI) after revision TKA. The cost of ciNPWT, cost of treatment for PJI, and baseline infection rates following revision TKA were collected from institutional data and the literature. The absolute risk reduction (ARR) in infection rate necessary for cost-effectiveness was calculated using break-even analysis. Using our institutional cost of ciNPWT ($600), this intervention would be cost-effective if the initial infection rate of revision TKA (9.0%) has an ARR of 0.92%. The ARR needed for cost-effectiveness remained constant across a wide range of initial infection rates and declined as treatment costs increased. The use of ciNPWT for infection prevention following revision TKA is cost-effective at both high and low initial infection rates, across a broad range of treatment costs, and at inflated product expenses.
Keywords: prosthetic joint infection; revision; total knee arthroplasty; cost; negative pressure wound therapy